Unfamous Beautiful Bonetambu Island In Makassar: Political, Economic, and Educational Perspectives - Yeyeng, Andi Tenri; Tajuddin, Muhammad Saleh; Latif, Muhlis (Lembaga Sembilan Tiga Community, 2024)
This research discusses the beauty of Bonetambu Island, which is less popular among local, national, and international communities from a political, economic, and educational perspective. This article is an initial introduction to this island, which has natural resource potential that can be managed well to improve community human resources. This paper uses qualitative research with data collection techniques through observation, interviews, and documentation. Secondary data was obtained through scientific journals, books, and the internet. The collected data was processed using Miles and Haberman's analytical techniques, starting with data verification, data display, and drawing conclusions. Results obtained from this article: 1) The people of Bonetambu Island do not yet have reliable political figures who can be launched as legislative candidates, they are only at the stage of supporting figures from outside the island. 2) Bonetambu Island has unique natural resource potential, especially the beauty of seabed coral reefs and the sunset to the west. The people of Bonetambu Island have a good work ethic but need to improve their skills in the field of fisheries with their main livelihood. 3) The educational facilities available on Bonetambu Island are only at the elementary and junior high levels, so very few people continue their education at the junior high school level or at Makassar College.